Inside the gamer's mind: How violent video games and emotional dysregulation affect EEG interbrain synchronization - Giorgio Veneziani; Federica Luciani; Marcello Miceli; Sara Spallaccini; Federica Galli; Lina Pezzuti; Carlo Lai (Computers in Human Behavior Reports, 2024)
Background: Exposure to violent video games influences players’ cortical activations. In addition, intra-individual variables like emotional regulation play an important role in the consequences of such exposures. However, most research has studied these relationships at the intra-individual level. Therefore, the present study investigated the effects of violent video games on the interbrain synchronization (IBS) of dyads in which one member played video games, and evaluated IBS differences between high and low-emotionally dysregulated groups. Methods: Eighteen participants (M = 24.1 ± 2.1) were enrolled in this study. Participants gazed into another person's eyes before playing (“First Direct Gaze”), after playing a violent video game (“Post-VV”), and after playing a nonviolent video game (“Post-NVV”) during an electroencephalographic hyperscanning acquisition. Afterward, each participant completed a socio-demographic questionnaire and the Difficulties in Emotion Regulation Scale. Results: A cluster-based analysis revealed an increased theta IBS Post-VV compared to Post-NVV. A median split was used to define the high emotionally dysregulated (“HED”) and low emotionally dysregulated (“LED”) groups. Results showed a decreased alpha IBS in the First Direct Gaze, Post-VV, and Post-NVV in the HED group compared to the LED group. Conclusions: Exposure to violent video games was associated with higher theta IBS, suggesting a greater social attunement, potentially due to a higher perceived dominance and control or due to an effort of managing the emotional activations elicited. In addition, difficulties in emotional regulation could elicit specific alpha activities regardless of exposure to a video game, leading to a lower tendency to attune with another person on this band.Results from this study should not be generalized to infer that playing any type of video game causes harm to people's brains.